Efficient adsorptive removal of levofloxacin using sulfonated graphene oxide: Adsorption behavior, kinetics, and thermodynamics - Chironjit Kumar Shaha; Subarna Karmaker; Tapan Kumar Saha (Heliyon, 2024)
Water pollution by antibiotic residues poses a potential threat to environmental and human health. Graphene-based materials are highly stable, recyclable and effective adsorbents for efficiently removing antibiotics from polluted water. In this study, the adsorption behavior of levofloxacin onto sulfonated graphene oxide (SGO) was investigated by varying the contact period, solution pH, adsorbent quantity, levofloxacin concentration, inorganic ions, and solution temperature. Spectroscopic and microscopic techniques were employed to confirm the adsorptive interaction between levofloxacin and SGO. The adsorption process was most accurately characterized by the pseudo-second-order kinetic model and the Langmuir isotherm model, as indicated by their high correlation coefficients (R2) and low root-mean-square error (RMSE) values. The maximal quantity of levofloxacin that can be adsorbed onto SGO was determined to be 1250 μmol/g at pH 4 and 25 °C using the Langmuir model. Thermodynamic studies reveal that the process of levofloxacin adsorption onto SGO is endothermic and spontaneous in nature. Taking into consideration the results of adsorption, desorption and regeneration studies, it is proposed that SGO can be applied as an economic viable agent for the adsorptive removal of levofloxacin from the aqueous environment.